Social Entrepreneurship in the Middle East Volume 1 - Jamali, Dima.; Lanteri, Alessandro; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This two-volume book unveils trends, strengths, weaknesses and overall dynamics and implications of social entrepreneurship in the Middle East region, whilst identifying both opportunities and threats facing social entrepreneurship and supplements through a wealth of insights and examples inspired from practice and current applications.
Keywords: Leadership; Small business; International business enterprises; Development economics; International economics; Entrepreneurship; Business Strategy/Leadership.; Small Business; International Business; Development Economics; International Economics; Entrepreneurship